THE CORRELATION BETWEEN THE DURATION OF PROTEASE INHIBITOR THERAPY AND INSULIN RESISTANCE AND TRIGLYCERIDE LEVELS IN PEOPLE WITH HIV/AIDS - Yuli Gayatri, Anak Agung Ayu; Kambayana, Gede; Subagiartha, Nyoman Agus; Junior, Rionaldo Anthonius De Quelyoe (Prosiding Seminar Nasional Sains dan Teknologi (Senastek), 2024)
The Human Immunodeficiency Virus (HIV) disease is a contagious disease and continues to be a global health issue. The widespread use of highly active retroviral therapy (HAART) led to a dramatic decrease in complications. However, on the other hand, the use of antiretroviral (ARV) drugs has raised concerns regarding metabolic disorders. Research on the effects of Protease Inhibitors (PIs), which are a type of HAART, on metabolic abnormalities is still very limited and controversial. Therefore, it is hoped that this study can be used as a reference in the management of HIV. An observational study with a cross-sectional design was conducted at the VCT outpatient clinic of Ngoerah General Hospital from March to July 2024. The study sample consisted of 70 HIV patients receiving protease inhibitor type ARV therapy. The statistical analysis used was the chi-square and logistic regression. The characteristics of the study subjects had the highest average age ranging from 40 - 44 years as many as 37 people (52.3%). The longest duration of use of antiretroviral drugs divided in the 6-12 months and more than 12 months. There was a significant correlation between the duration of ARV treatment with insulin resistance and increase in triglycerides level. There is a significant correlation between the duration of ARV treatment with insulin resistance and increase level of triglycerides. The longer duration of use of Protease Inhibitor, the further it will increase the insulin resistance and triglycerides level.